A study of intra-operative maternal morbidity after repeating caesarean section - Somani, Sonali S.; Sudhir, Sunita; G. Somani, Shashikant; Bushra, . (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Caesarean section (CS) is one of the most common obstetric procedures worldwide and an increased rate of caesarean section has been observed in recent studies. Maternal morbidities and mortality associated with repeat caesarean section is an important health problem. The present study aims at knowing the various intraoperative complications encountered during repeat caesarean sections. Objective was to study the incidence and type of surgical difficulties encountered in repeat cesarean sections Methods: It was a prospective observational study of 118 cases of repeat cesarean sections. Intra-operative findings of all cases were analyzed to know the difficulties encountered because of previous cesarean section. Results: In present study, out of total 118 cases of previous cesarean sections, 71 (60.17%) cases were of previous one caesarean section and 47(39.83%) were of previous two cesarean sections. Following intraoperative morbidities were encountered – adhesions (1 caesarean section vs 2 caesarean section – 40.85 vs 65.96% respectively) , thin lower uterine segment (1 caesarean section vs 2 caesarean section – 21.13 vs 36.17% respectively), advanced bladder(1 caesarean section vs 2 caesarean section – 15.49 vs 36.17 % respectively) , extension of uterine incision(1 caesarean section vs 2 caesarean section – 9.86 vs 19.15% respectively) , scar dehiscence(1 caesarean section vs 2 caesarean section –7.04 vs 31.91% respectively), excess blood loss (1 caesarean section vs 2 caesarean section –7.04 vs 19.15% respectively), 1 case of placenta accrete was found in previous 2 caesarean section 2.13%) which needed caesarean hysterectomy. uterine rupture and bladder injury seen in one patients of previous 2caesarean section. Time taken for surgery was more in repeat CS group Delivery. Conclusions: An increasing number of CS is accompanied by increased maternal morbidity. Intraoperative complication which increase the risk of morbidity are adhesion, placenta accreta. It is prudent to involve a senior experienced obstetrician in repeat cesarean section. The best way to reduce this is by reducing primary caesarean section rates. Patients with previous caesarean section should be considered as high risk and should be counseled for regular antenatal check-up and they should be given option of vaginal birth after CS whenever possible.